Atomic-resolution investigations on formation and evolution of symmetric tilt grain boundaries near the 101¯2 twin orientation in a Mg alloy. (October 2020) - Su, Huhu; Zhou, Xinzhe; Zheng, Shijian; Wu, Di; Chen, Rongshi; Ye, Hengqiang; Yang, Zhiqing
Abstract: Formation and evolution of symmetric tilt grain-boundaries (STGBs) near the 10 1 ¯ 2 twin orientation in a Mg alloy were studied with atomic-resolution. The STGBs could be formed by reactions of 10 1 ¯ 2 twin boundaries with 60° basal dislocations (referred to as 〈a 60 〉) coming respectively from the twin and matrix, with each pair of 〈a 60 〉 forming a grain-boundary dislocation (GBD). Incident 〈a 60 〉 dislocations reacted with GBDs, consequently activating emission of twinning dislocations which resulted in migration of the STGBs. Interestingly, STGBs could be transformed into 10 1 ¯ 2 twin boundaries by either grain-boundary sliding or reacting with an array of basal 〈a 60 〉 dislocations. Graphical abstract: Image, graphical abstract